Electronic Spectra of Mixed Ligand Complexes of Copper(II) with Different Amino Acids - Shailja Nigam, Mrs.; Mohabey, Miss. Hemlata (Asian Journal of Chemistry, 2010)
Copper(II) complexes were synthesised using methionine as the common ligand and proline and serine as secondary ligands. The mixed ligand complexes are soluble in water. Their electronic spectra was scanned in water. Both the complexes show one asymmetric absorption band around 16,000 cm-1 , which suggests that these mixed complexes have distorted octahedral geometry. Since single band is observed in the electronic spectra of both the newly synthesised copper(II) complexes, trans-geometry is suggested. The value of molar extinction coefficient does not alter by change in concentration hence it is confIrmed that complexes do not undergo association or dissociation in solution.